PERBEDAAN WARNA LAMPU TERHADAP JUMLAH LALAT YANG TERPERANGKAP (TREE FLY LIGHT TRAPS) DI PANTRY INDUSTRI PANGAN (Politeknik Kesehatan Kemenkes Bandung, 2021)
Flies are one of the vectors that cause disease in humans. The disease is a digestive tract infection (dysentery, diarrhea, typhoid, cholera and certain helminth infections). The purpose of this study was to analyze the number of trapped flies and to analyze the difference in the color of red, yellow, and white lights to the number of trapped flies. This type of research is an experimental research design with post test with control. The sample in this study was the Musca domestica fly. The independent variable is the variation of the color of the trap lights, namely red, white and yellow, the dependent variable is the number of trapped flies. The sampling technique was incidental sampling. The treatment given was 3 (three) treatments, namely the color of the light yellow, white and red. Observational data were analyzed using Kruskal Wallis there was a significant difference in the number of trapped flies based on the color of the lamp with a P value of 0.001. The results of the measurement of the number of flies trapped were more in red lights, namely 41 birds, compared to yellow (32 tails) and white (23 tails).